Simulation of assembly line for production performance improvement - Mohd Saiful Akmal, Razali (2016)
An automotive assembly line is a process in automotive manufacturing system whereby car parts are installed and the semi-finished car body moves from a workstation to another workstation in sequencing manners until the final assembly of the car is produced. This Bachelor Thesis presents the study of the automotive assembly line at the Trim-ChassisFinal Line in a particular automotive manufacturing organization in Malaysia. The objectives of this study are to perform simulation study, evaluate the performance of the current production system and identify the root cause of the problem. The production data were collected and simulated using discrete event simulation. In this project, Siemens Tecnomatix Plant Simulation is used to simulate and optimize the production layout. Then, three improvement strategies are proposed and simulated in order to identify the effect of the improvement strategies on the production performance. The strategies consist of eliminating non-value added sub-processes to the line, adding sub-processes to the line. Elimination of the non-value added sub-processes to the line will reduce the working, picking and walking times. Meanwhile, addition of sub-processes to the line will increase the working, picking and walking times. Simulation results indicate that all of the improvement strategies are able to maximize the productivity and line efficiency, but only one improvement strategy with greater significance will be chosen. This proposed improvement strategy has a better line efficiency and throughput per shift compared to the current production layout and another two improvement strategies.